2009
DOI: 10.1177/1532673x09353509
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Party Factions in American Politics

Abstract: What are the primary factions within the Democratic and Republican parties, and to what extent do rival factions cooperate? We address these questions using a unique data set of information sharing between party organizations, media outlets, 527s, and interest groups. Using social network methods, we identify two major information-sharing clusters, or expanded party networks; these networks correspond to a liberal/Democratic grouping and a conservative/Republican grouping. We further identify factions within e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 19 publications
1
64
0
Order By: Relevance
“…Research shows that some elements of the PAC community behave as partisans, as demonstrated by a willingness to support challengers of one party (Brunell 2005). As mentioned previously, an emerging theoretical perspective posits that subsets of PACs, interest organizations and officeholders constitute an extended party network that shares information (Koger, Masket, and Noel 2009;Koger, Masket, and Noel 2010), and endorses and contributes to the same candidates (Grossmann and Dominguez 2009;Bawn et al 2012;Heaney et al 2012;Skinner, Masket, and Dulio 2012).…”
Section: Interest Groupsmentioning
confidence: 99%
“…Research shows that some elements of the PAC community behave as partisans, as demonstrated by a willingness to support challengers of one party (Brunell 2005). As mentioned previously, an emerging theoretical perspective posits that subsets of PACs, interest organizations and officeholders constitute an extended party network that shares information (Koger, Masket, and Noel 2009;Koger, Masket, and Noel 2010), and endorses and contributes to the same candidates (Grossmann and Dominguez 2009;Bawn et al 2012;Heaney et al 2012;Skinner, Masket, and Dulio 2012).…”
Section: Interest Groupsmentioning
confidence: 99%
“…Examples of recent research using this approach include studies of international conflict (Hafner-Burton & Montgomery, 2006), legislative cosponsorship (Fowler, 2006), caucuses in the U. S. Congress (Victor & Ringe, 2009), multiplex interest group and political party networks (Grossman & Dominguez 2009;Koger et al, 2010), and the rise of institutional innovations during the Renaissance in Florence (Padgett & McLean, 2006). In these cases, the observed actors do not have the opportunity to react to the research and, thus, cannot cause the reported structure of the network.…”
Section: Obtrusive Versus Unobtrusive Methodsmentioning
confidence: 99%
“…Social network ties may prompt people to vote (Nickerson, 2008). They influence legislative cooperation on bill sponsorship (Fowler, 2006), party cooperation across competing factions (Grossman & Dominguez, 2009;Koger, Masket, & Noel, 2010;Schwartz, 1990), and social movement cooperation across coalition boundaries (Heaney & Rojas, 2007. The degree of influence that interest groups have in the legislative process depends, in part, on their access to networks of other interest groups (Carpenter, Esterling, & Lazer, 2004;Heinz, Laumann, Nelson, & Salisbury, 1993;Laumann & Knoke, 1987).…”
Section: By Michael T Heaneymentioning
confidence: 99%
“…In one archetypal application of social-network analysis, for example, we may observe clusters of smokers and of nonsmokers because smoking is contagiousone acquires the habit from friends or avoids acquisition because one's friends abstain-or because smokers choose to hang with smokers and nonsmokers with nonsmokers: homophily by behaviortype-or we may observe clustering of smokers and nonsmokers because both the behavior of (non)smoking and the connections between mutually (non)smoking behavior-types are caused by actors' common exposure to outside conditions, such as shared sociodemographics that affect both the propensity to smoke and friendship formation. To give a more political example (expanded from Koger et al (2009Koger et al ( , 2010): representatives who sit together may vote similarly because they sit by party and so have similar constituencies (common exposure), or because they talk and influence each other (contagion), or they may choose to sit together because they know and like each other, which may be in some part because they vote similarly (selection). Or, to give the example from our empirical application, international conflict may be contagious through alliance connections, but nations that have similar conflict-behavior patterns are also more likely to ally (selection), and both alliance and conflict patterns may be affected the same exogenous conditions to which particular nation-state dyads are exposed, such as their contiguity.…”
Section: Introductionmentioning
confidence: 99%